Characterization and Experimental Investigation of NaNO3: KNO3 as Solar Thermal Energy Storage for Potential Cooking Application - Wagari, Elias; Aman, Abdulkadir; Sahu, Omprakash (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
Household cooking is a major energy intensive activity in most of the Ethiopian households. Replacing the existing inefficient cooking stoves and the polluting energy source with a renewable source of energy plays a paramount role in conserving the environment and reducing the indoor pollution. In this study an energy storage phase change material is proposed to store solar thermal energy for a potential household cooking application. The selected phase change material has a melting point range which is well fitted to the operating range of temperatures for most of the household cooking activities. The solar energy source is simulated with electrical heating for experimental investigation of the thermal characteristics. Also it is intended to study the thermal characteristics of the mixture using deferential scanning calorimeter to identify at which mass ratio the mixture shows better thermal characteristics. From the laboratory analysis it is found that the 60% NaNO3 and 40% KNO3 by mass has shown promising thermal characteristics. For applying the selected salt mixture for cooking application, an experiment was conducted on two Ethiopian local meals, shiro wet and potato meal, to know how much energy is required to cook them and what amount of the PCM is required to store the required energy. The result reveals that 2.38KwH energy is required for cooking the two meals for five family members for lunch and dinner. To store the energy required 4kg of the PCM was required. Experiments were conducted to see the charging and discharging time of 60% NaNO3 and 40% KNO3 by mass. From the experimental result for 1.4kg of the PCM, charging time of 50 minutes up to 300oC a discharging time of 4.5 hours (From 300oC -100oC) is required.